Prevalence of Plasmodium falciparum Parasitaemia and Its Correlation with Haematological Parameters among HIV-Positive Individuals in Nigeria - Olusola Ojurongbe; Oluwatoyin Adeola Oyeniran; Oyebode Armstrong Terry Alli; Sunday Samuel Taiwo; Taiwo Adetola Ojurongbe; Adekunle Olugbenga Olowe; Oluyinka Oladele Opaleye; Oluwaseyi Adegboyega Adeyeba (Journal of Tropical Medicine)
Malaria and HIV are the two most important health challenges of our time. Haematologic abnormalities are features in Plasmodium falciparum infection, and anaemia is a well-known outcome. The prevalence and haematological impact of P. falciparum parasitaemia were determined among HIV-infected individuals in Nigeria. Parasite detection was carried out using microscopy and Polymerase Chain Reaction (PCR). Haemoglobin concentration was determined using an automated machine while CD4+ T-cells count was analyzed using flow cytometer. Thirty-seven (18.5%) out of the 200 HIV individuals enrolled had malaria parasites detected in their blood. All the positive cases were detected by PCR while only 20 (10%) were detected by thick blood microscopy. The mean haemoglobin concentration and packed cell volume (PCV) of HIV individuals with malaria parasitaemia were lower compared to those without malaria parasitaemia but the difference was not statistically significant. Also no significant difference was observed in malaria positivity in respect to sex and mean CD4+ cell count. The study highlights the effects of P. falciparum parasitaemia on the haematologic and immune components of HIV individuals.